Self-insertion of foreign body (hairpin) in urethra and its removal by non-operative technique - Vishal, Vaibhav; Darsan, Lal; M, Manikandan; AV, Venugopalan; Cardoza, Felix (Indian Journal of Case Reports, 2019)
A urethral foreign body is usually found as a part of sexual misadventure mostly in a young male. The literature has described items like a fork, battery, wire and other things in the urethra which almost always required a surgical procedure for its removal. Here we present the case of self-insertion of a hairpin in the male urethra with the open pointed end of hairpin facing distally. The hairpin despite being “stuck” inside the urethra due to its sharp end embedded in urethral mucosa was successfully removed with simple manipulation techniques with no complication in follow-up. This case highlights the point that when faced with the situation of an uncommon object in the urethra, the treatment has to be individualized according to the type of object, age and sex of the patient and sometimes common unorthodox technique can save the patient from operative procedure.